1986
DOI: 10.1084/jem.163.6.1363
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor/cachectin interacts with endothelial cell receptors to induce release of interleukin 1.

Abstract: Tumor necrosis factor/cachectin (TNF) has been implicated as a mediator of the host response in sepsis and neoplasia. Recent work has shown that TNF can modulate endothelial cell hemostatic properties, suggesting that endothelium is a target tissue for TNF. This led us to examine whether endothelial cells have specific binding sites for TNF and augment the biological response to TNF by elaborating the inflammatory mediator, IL-1. Incubation of 125I-recombinant human TNF with confluent, cultured human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
207
2
8

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(225 citation statements)
references
References 34 publications
8
207
2
8
Order By: Relevance
“…28,29 It is well known that TNF-a can induce the expression of endothelial adhesion molecules involved in the migration of leukocytes to extravascular sites of inflammation as well as stimulate the release of other proinflammatory cytokines. 30,31 Genetically engineered fusion proteins consisting of two identical chains of the recombinant soluble TNF-receptor (sTNFR) monomer fused with the Fc domain of IgG1 have been developed for the treatment of TNF-associated diseases. 14,32 In this study, we demonstrated that electrotransfer of sTNFR:Fc DNA could reduce the incidence of CIA and the levels of IL-1b and IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 It is well known that TNF-a can induce the expression of endothelial adhesion molecules involved in the migration of leukocytes to extravascular sites of inflammation as well as stimulate the release of other proinflammatory cytokines. 30,31 Genetically engineered fusion proteins consisting of two identical chains of the recombinant soluble TNF-receptor (sTNFR) monomer fused with the Fc domain of IgG1 have been developed for the treatment of TNF-associated diseases. 14,32 In this study, we demonstrated that electrotransfer of sTNFR:Fc DNA could reduce the incidence of CIA and the levels of IL-1b and IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present findings concerning keratinocyte TNF-a release, the constitutive production of these factors both in vitro and in vivo is very low and has tobe induced by various stimuli, including bacterial or viral products, tumor promotors, UV light, or cytokines themselves. TNF-a hasbeen demonstrated to stimulate the release of other mediators, such as I1J1, IIr6, IIr8, granulocyte/macrophage (GM)-CSF, and platelet-derived growth factor in various cell types (24)(25)(26)(27), and thus appears to be a key member of the cytokine cascade, playing an important role in pathologic events accompanying invasion of foreign organisms. Since the epidermis is frequently in contact with environmental microorganisms, it is not surprising that epidermal cells appear to be endowed with the capacity to release TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Since solar exposure can cause a significant inflammatory response in the skin, TNF-a may be involved in the mediation of this local reaction directly or via induction of other cytokines (24)(25)(26)(27) . In addition, this study demonstrates that after extensive UV exposure, increased TNF-a levels can be detected in the circulation and thus may be responsible for systemic effects .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, thrombomodulin binds to serum proteins S and C to promote local anti-coagulation. This finding, in association with the capacity of TNF to induce inflammatory cell adherence to vessel walls (Nawroth & Stern, 1986;Taylor et al, 1987), represents an additional factor contributing to a coagulant state with cessation of blood flow and then leading to tissue necrosis.…”
Section: General Properties Of Tnfmentioning
confidence: 99%